The staple food economies of western tropical Africa - Johnston, Bruce F. (Stanford, Calif. : Stanford University Press, 1958)
The purpose of this study is to present a broad picture of the staple food crops of major importance in African agriculture and diets. The work is based primarily on published materials, a four month trip in early 1958 to West and Central Africa, and London, Brussels, Paris, and Rome afforded opportunities to complete and verify many points and to correct a number of erroneous impressions and interpretations.
Includes bibliographical references and index.
hza 28/01/2019
Loans
Keywords: Agriculture; Agricultural Economies; Food supply